Glenndalocha (Glendalough) - stolica tytularna biskupa Mariana Przykuckiego, sufragana poznańskiego - Prokop, Krzysztof R. (Poznańskie Studia Teologiczne, 2012)
Glendalough („glen of two lakes”), an Irish bishopric since the beginning of the 7th century, united with the archdiocese of Dublin at the beginning of the 13th century, since 1969 included among titular sees. In the years 1973-1981 it was the titular see of bishop Marian Przykucki, the suffragan bishop of Pozna? and later the bishop of the Che?mno (1981-1992) and the Szczecin- -Kamie? (1992-1999) dioceses.